Nanotheranostics for Image-Guided Cancer Treatment - Isabel S. Dennahy; Zheng Han; William M. MacCuaig; Hunter M. Chalfant; Anna Condacse; Jordan M. Hagood; Juan C. Claros-Sorto; Wajeeha Razaq; Jennifer Holter-Chakrabarty; Ronald Squires; Barish H. Edil; Ajay Jain; et al. (MDPI AG, 2022)
Image-guided nanotheranostics have the potential to represent a new paradigm in the treatment of cancer. Recent developments in modern imaging and nanoparticle design offer an answer to many of the issues associated with conventional chemotherapy, including their indiscriminate side effects and susceptibility to drug resistance. Imaging is one of the tools best poised to enable tailoring of cancer therapies. The field of image-guided nanotheranostics has the potential to harness the precision of modern imaging techniques and use this to direct, dictate, and follow site-specific drug delivery, all of which can be used to further tailor cancer therapies on both the individual and population level. The use of image-guided drug delivery has exploded in preclinical and clinical trials although the clinical translation is incipient. This review will focus on traditional mechanisms of targeted drug delivery in cancer, including the use of molecular targeting, as well as the foundations of designing nanotheranostics, with a focus on current clinical applications of nanotheranostics in cancer. A variety of specially engineered and targeted drug carriers, along with strategies of labeling nanoparticles to endow detectability in different imaging modalities will be reviewed. It will also introduce newer concepts of image-guided drug delivery, which may circumvent many of the issues seen with other techniques. Finally, we will review the current barriers to clinical translation of image-guided nanotheranostics and how these may be overcome.